(untitled) (Research, Society and Development, 2023)
Purpose: To describe which predictive reading and writing skills are most effective in identifying students with learning difficulties in the first and second year of Elementary School I. Methods: 68 students took part in, divided into two paired groups: students with learning difficulties in the 1st and 2nd year of Elementary School I (G1) and students without complaints of learning difficulties (G2). The students were assessed in writing level and predictive linguistic, auditory and phonological processing skills. Results: G1 students showed lower performance in the writing level and expressive vocabulary skills, phonological verbal fluency, memory of verbal sounds, memory of simple orders, auditory verbal discrimination, phonological awareness, phonological working memory and phonological access to the mental lexicon compared to G2. As for the skills of the phonological system, semantic verbal fluency, auditory perception, sound localization, memory of non-verbal sounds and memory of complex orders, there was no difference between the groups. Conclusion: Students in the initial phase of literacy with learning difficulties showed lower performance in the writing level and in most of the predictive skills, when compared to students without complaints of learning difficulties, showing signs of risk for this alteration. This work can contribute to health and education professionals who seek to reduce the impact of low academic performance on the child’s quality of life, as it provides subsidies to develop identification, promotion and early intervention programs, based on the predictive skills of reading and writing in the years beginnings of literacy.